Monoglyceride lipase deficiency modulates endocannabinoid signaling and improves plaque stability in ApoE-knockout mice. (January 2016) - Vujic, Nemanja; Schlager, Stefanie; Eichmann, Thomas O.; Madreiter-Sokolowski, Corina T.; Goeritzer, Madeleine; Rainer, Silvia; Schauer, Silvia; Rosenberger, Angelika; Woelfler, Albert; Doddapattar, Prakash; Zimmermann, Robert; Hoefler, Gerald; et al.
Abstract: Background and aims: Monoglyceride lipase (MGL) catalyzes the final step of lipolysis by degrading monoglyceride (MG) to glycerol and fatty acid. MGL also hydrolyzes and thereby deactivates 2-arachidonoyl glycerol (2-AG), the most abundant endocannabinoid in the mammalian system. 2-AG acts as full agonist on cannabinoid receptor type 1 (CB1R) and CB2R, which are mainly expressed in brain and immune cells, respectively. Thus, we speculated that in the absence of MGL, increased 2-AG concentrations mediate CB2R signaling in immune cells to modulate inflammatory responses, thereby affecting the development of atherosclerosis. Methods and results: We generated apolipoprotein E (ApoE)/MGL double-knockout (DKO) mice and challenged them with Western-type diet for 9 weeks. Despite systemically increased 2-AG concentrations in DKO mice, CB2R-mediated signaling remains fully functional, arguing against CB2R desensitization. We found increased plaque formation in both en face aortae (1.3-fold, p = 0.028) and aortic valve sections (1.5-fold, p = 0.0010) in DKO mice. Interestingly, DKO mice also presented reduced lipid (12%, p = 0.031) and macrophage content (18%, p = 0.061), elevated intraplaque smooth muscle staining (1.4-fold, p = 0.016) and thicker fibrous caps (1.8-fold, p = 0.0032), together with a higher ratio of collagen to necrotic core area (2.5-fold, p = 0.0003) and expanded collagen content (1.6-fold, p = 0.0007), which suggest formation of less vulnerable atherosclerotic plaques. Treatment with a CB2R inverse agonist prevents these effects in DKO mice, demonstrating that the observed plaque phenotype in DKO mice originates from CB2R activation. Conclusion: Loss of MGL modulates endocannabinoid signaling in CB2R-expressing cells, which concomitantly affects the pathogenesis of atherosclerosis. We conclude that despite larger lesion size loss of MGL improves atherosclerotic plaque stability. Thus, pharmacological MGL inhibition may be a novel intervention to reduce plaque rupture. Graphical abstract: Highlights: Plasma, aortic, and macrophage 2-AG levels are increased in ApoE/MGL-DKO mice. Desensitization of CB1R but not CB2R occurs in DKO mice. DKO mice develop less vulnerable atherosclerotic lesions. CB2R antagonist treatment reverses plaque phenotype in DKO mice.